The Spiral Coaxial Cable. (26th February 2015) - Fabbri, I. M.
Abstract : A new concept of metal spiral coaxial cable is introduced. The solution to Maxwell's equations for the fundamental propagating TEM eigenmode, using a generalization of the Schwarz-Christoffel conformal mapping of the spiral transverse section, is provided together with the analysis of the impedances and the Poynting vector of the line. The new cable may find application as a medium for telecommunication and networking or in the sector of the Microwave Photonics. A spiral plasmonic coaxial cable could be used to propagate subwavelength surface plasmon polaritons at optical frequencies. Furthermore, according to the present model, the myelinated nerves can be considered natural examples of spiral coaxial cables. This study suggests that a malformation of the Peters angle, which determines the power of the neural signal in the TEM mode, causes higher/lower power to be transmitted in the neural networks with respect to the natural level. The formulas of the myelin sheaths thickness, the diameter of the axon, and the spiralg factor of the lipid bilayers, which are mathematically related to the impedances of the spiral coaxial line, can make it easier to analyze the neural line impedance mismatches and the signal disconnections typical of the neurodegenerative diseases.